Proses Strategi Distribusi Produk Susu Fisian Flag Oleh PT Adam Dani Lestari - Felice Mareta Waruwu; Natanael Simanjuntak; Yolanda Sarumaha (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research was conducted at PT ADAM DANI LESTARI with the formulation of the problem is how the distribution strategy process of Frisian Flag products. The purpose of this study is to determine the distribution strategies of Frisian Flag products. The data used in writing this journal were collected through interviews and analyzed using qualitative description methods. The results of this study concluded that the distribution strategy process of Frisian Flag Milk products carried out by PT ADAM DANI LESTARI uses a direct distribution strategy to dominate the market and face competitors. However, in order to increase the brand and customer value, the company uses wholesalers and retailers so that products can be sold and delivered to consumers properly and maintain the availability of Frisian Flag Milk products in Medan City.